2022
DOI: 10.4103/tcmj.tcmj_145_22
|View full text |Cite
|
Sign up to set email alerts
|

Stem-cell therapy in stress urinary incontinence: A review

Abstract: A BSTRACT The incidence of urinary incontinence (UI) is approximately 10%–40% in women, affecting one to two hundred million women worldwide. Stress UI (SUI) is characterized by involuntary urination due to increased abdominal stress and urine leakage without bladder contraction. Surgical treatments include midurethral slings, bulking agents, and Burch colposuspension to restore urethral continence. Nevertheless, an optimal treatment for all types of incontinence has not yet been estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…These sources include adult and fetal tissues and human embryonic stem cells (hESCs). Although clinical trials with stem cell therapy have been reported in erectile dysfunction, 10 stress urinary incontinence, 11 and detrusor underactivity, 12 none have been conducted for IC/BPS in the field of urology.…”
Section: Why Is Stem Cell Therapy a Potential Candidate For Interstit...mentioning
confidence: 99%
“…These sources include adult and fetal tissues and human embryonic stem cells (hESCs). Although clinical trials with stem cell therapy have been reported in erectile dysfunction, 10 stress urinary incontinence, 11 and detrusor underactivity, 12 none have been conducted for IC/BPS in the field of urology.…”
Section: Why Is Stem Cell Therapy a Potential Candidate For Interstit...mentioning
confidence: 99%
“…Nevertheless, an optimal treatment for all types of incontinence has not been established. 1,2 Continence and micturition are achieved by a complex interplay of anatomical structures such as the urethral sphincter, detrusor, bladder neck, urethral smooth muscle, nerves, vascular plexus and the surrounding tissue support. There is an active and passive component contributing to intraurethral pressure.…”
Section: Introductionmentioning
confidence: 99%